Feasible kidney donation with living marginal donors, including diabetes mellitus. Issue 3 (8th June 2021) - Yoshinaga, Kasumi; Araki, Motoo; Wada, Koichiro; Sekito, Takanori; Watari, Shogo; Maruyama, Yuki; Mitsui, Yosuke; Sadahira, Takuya; Kubota, Risa; Nishimura, Shingo; Edamura, Kohei; Kobayashi, Yasuyuki; et al.
Abstract: Objectives: To compare the donor outcomes of living donor kidney transplantation between standard donors (SDs) and marginal donors (MDs) including diabetic patients (MD + DM). Methods: MDs were defined according to Japanese guideline criteria: (a) age >70‐years, (b) blood pressure ≤130/80 mmHg on hypertension medicine, (c) body mass index >25 to ≤32 kg/m 2, (d) 24‐h creatinine clearance ≥70 to <80 ml/min/1.73 m 2, and (e) hemoglobin A1c > 6.2 or ≤6.5 with oral diabetic medicine. Fifty‐three of 114 donors were MDs. We compared donor kidney functions until 60 months postoperatively. Results: No kidney function parameters were different between SDs and MDs. When comparing SD and MD + DM, MD + DM had a lower postoperative eGFR (48 vs. 41 (1 (month), p = .02), 49 vs. 40 (12, p < .01), 48 vs. 42 (24, p = .04), 47 vs. 38 (36, p = .01)) and the percentage of residual eGFR (SD vs. MD + DM: 63 vs. 57 (1 (month), p < .01), 63 vs. 57 (2, p < .01), 64 vs. 56 (12, p < .01), 63 vs. 57 (24, p < .01), 63 vs. 52 (36, p = .02)). However, when MD with a single risk factor of DM was compared to SD, the difference disappeared. Nine out of 12 (75%) MD + DM had ≥2 risk factors. Conclusions: Although long‐term observation of donor kidney function is necessary, careful MD + DM selection had the potential to expand the donor pool. Abstract : This study demonstrates the safety and potential of kidney donations for marginal donors. Careful Mmarginal donors with diabetes mellitus selection has the potential to expand the donor pool.